Licensing of public plant varieties: the case of CSIR - Kuhlmann, Katrin; Nalinya, Adron Naggayi; Botey, Mireku; Puozaa, Doris Kanvenaa; Gichuru, Lilian; Ojiewo, Chris Ochieng (CIMMYT, 2025)
To achieve sustained productivity growth, it is critical that farmers adopt improved crop varieties alongside sound agronomic practices. The Council for Scientific and Industrial Research (CSIR), through its Crops Research Institute (CRI) and Savanna Agricultural Research Institute (SARI), leads the conduct and coordination of breeding and related research focused on developing crops suited to different agroecological zones with consumer preferred traits. However, unpredictable funding and limited dissemination capacity often prevent these innovations from reaching smallholder farmers who depend on them at scale In response to these challenges, CSIR is increasingly exploring licensing as a way to stimulate the commercialization of its agricultural technologies. This approach aligns with CSIR’s broader mandate to enhance the impact of its research by fostering collaboration with the private sector. Licensing agreements could offer a viable path for public varieties to enter the market, potentially generating royalty income that could be reinvested into further research and varietal promotion activities. This could also help ensure that farmers have access to the latest, most effective varieties. However, the process of licensing public varieties is far from straightforward. While there is potential for licensing models to accelerate the commercialization of improved varieties, their success depends on overcoming several key barriers. Licensing agreements must be structured in a way that is attractive to the private sector, while also safeguarding the public interest and public good nature of some technologies. Public research institutions, such as CSIR, need to navigate the complex intersection of intellectual property rights, legal and regulatory frameworks, and market dynamics. The importance of this issue has been recognized by the New Markets Lab (NML) and the Dryland Crops Program of the International Maize and Wheat Improvement Center (CIMMYT), as part of the implementation of the Accelerated Varietal Improvement and Seed Delivery of Legumes and Cereals in Africa (AVISA) project, have worked to build capacity and share knowledge with key stakeholders in Ghana. These efforts have focused on supporting the CSIR in fostering the adoption of improved varieties by both the private sector and farmers. This report on the licensing of public varieties by CSIR builds upon a body of work previously conducted by NML in countries such as Tanzania, Nigeria, Kenya, Uganda, Senegal, and Mali,1 in collaboration with other partners, including CIMMYT, the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), the International Institute of Tropical Agriculture (IITA), the International Center for Tropical Agriculture (CIAT), and the Syngenta Foundation for Sustainable Agriculture (SFSA). Through the AVISA project, NML has developed several resources to guide the licensing process. These include an Annotated Guide on Flexible Licensing Models and Agreements, which outlines various options for structuring licensing agreements and includes examples of potential provisions; Tanzania and Nigeria Guidebooks for Regulatory Aspects of Disseminating Public Varieties,2 which examine the regulatory frameworks in both countries and their relevance to the licensing of public varieties; and Model Plant Variety Licensing Agreements tailored to the specific regulatory environments of Tanzania and Nigeria. This report critically examines CSIR’s nascent efforts on licensing its varieties. It assesses current approaches, evaluating both successes and shortcomings. While CSIR has made notable strides since reinitiating its licensing program in 2022 and expanding it in 2024, several gaps remain, particularly in terms of institutional capacity, awareness among stakeholders, and the alignment of legal and regulatory instruments with market needs. The report also identifies key challenges, such as the need for more robust public-private partnerships, more comprehensive training for researchers and stakeholders, and clearer guidelines for navigating the complex legal and regulatory landscape and licensing processes. The findings and recommendations contained in the report are based on semi-structured consultations with nearly 40 stakeholders from CSIR who engaged in NML-led licensing workshops in Kumasi and Tamale. These included breeders, management teams, plant variety protection desk officers, legal representatives from CRI and SARI, and representatives from the private sector. Key recommendations for enhancing the effectiveness of CSIR’s licensing efforts include: Establishing Multi-tiered Capacity-building Strategy: Capacity building is needed at multiple levels, so a multi-tiered capacity building strategy could be developed to go beyond basic workshops and include practical, hands-on training in licensing negotiations, intellectual property and related law, and market access. This could include leveraging digital tools, such as the one under development by NML, to provide continuous access to capacity building tools and professional development through follow-up sessions and mentorship to ensure that knowledge is applied effectively and that stakeholders stay up to date with evolving standards in licensing practices. Formal EGS Supply Processes with Streamlined Distribution and Focus on Strengthening Infrastructure and Human and Financial Capacity: CSIR could collaborate with the Ministry of Food and Agriculture (MOFA) and seed companies to obtain production data for better demand forecasting and supply alignment. This could include use of digital platforms for advance ordering and payment to improve EGS production planning, creation of a registry to track breeder lines and licensed varieties, improved internal quality assurance mechanisms for EGS production, and sustainable financing through public-private partnerships or donors. Capacity Building on Intellectual Property Rights and Intellectual Asset Management for Public and Private Stakeholders: Capacity building in legal aspects of intellectual property and intellectual asset management would be beneficial to CSIR’s future work on licensing. Internally, CSIR could establish comprehensive DUS protocols for more crops, especially in AVISA focus area, and advocate for waiver of PVP registration fees for public varieties to reduce financial burdens and encourage innovation, with a focus on PVP for varieties that have the most market potential. Licensing Strategy for CRI and SARI for Varietal Promotion: A licensing (and funding) strategy should be developed for CRI and SRI, including in collaboration with the private sector, to share promotion costs by leveraging innovative licensing models. These could include lower royalty rates for companies that commit to investment in varietal promotion and promotion of a demand-led breeding approach, including collaboration with experts from other fields (e.g., gender, socio-economic studies) to ensure that varieties meet diverse farmer and consumer needs. Variety Licensing Database: A variety licensing database could be developed that includes up-to-date information on all available varieties, their traits, suitable growing conditions, and their licensing status (including whether they are protected under PVP). This database should be easily accessible by both public institutions and private sector stakeholders, with a user-friendly interface that allows for seamless access to information. Once created, the database should be regularly updated to reflect new varieties, changes in licensing agreements, and market trends. Further, CSIR could focus on creating a dynamic system for feedback from private sector actors to ensure that the varieties listed align with market needs, improving the flow of relevant information. Standardized Licensing Guidelines: Standardized licensing guidelines should be developed across the relevant CSIR institutes. This process could be expedited through collaboration between CRI and SARI to ensure that the guidelines are harmonized, transparent, and easily accessible to potential licensees. The guidelines should clearly specify the required documentation, application procedures, and the responsibilities of both the licensor and licensee. A clear, well-publicized licensing process will not only streamline the application process but also enhance the confidence of private sector stakeholders in engaging with public sector innovations. Capacity Building for Private Seed Companies: Capacity building support for the private sector should cover some of the same issues noted above. It could also include matched financial support, infrastructure development, and training in formal business practices. This would enable seed companies to independently produce EGS and engage in formal licensing processes, fostering a more sustainable and growth-oriented seed sector in Ghana.